Why do we not want to recommend influenza vaccination to young children? A qualitative study of Australian parents and primary care providers. Issue 6 (1st February 2018) - Biezen, Ruby; Grando, Danilla; Mazza, Danielle; Brijnath, Bianca
Highlights: Despite proven safety of influenza vaccines, uptake in young children is low. Reasons for low uptake included negative publicity and lack of awareness of benefits. Uncertainty of vaccine safety and efficacy led to reluctance to recommend by PCPs. Interventions should target parental knowledge and update information to PCPs. Including influenza vaccination in childhood immunisation schedule may increase uptake. Abstract: Introduction: Influenza vaccination has been shown to be safe and effective against influenza and in the prevention of complicating secondary respiratory illnesses. However, its uptake in young children remains low. This study explored the views, attitudes and practices of parents and primary care providers (PCPs) on their knowledge and acceptance of influenza vaccination in children under 5. Methods: Using a cross-sectional qualitative research design, we conducted 30 in-depth interviews with PCPs (i.e., general practitioners, practice nurses, maternal and child health nurses, and pharmacists) and five focus groups with parents (n = 50) between June 2014 and July 2015 in Melbourne, Australia. Data were thematically analysed. Results: Parents thought the vaccine could cause influenza, and influenza vaccination was not necessary for their children as they needed to build their own 'immunity'. Parents said that they would consider vaccinating their children if recommended by their GP and if the influenza vaccine was part of the immunisation schedule. PCPs also expressed concerns regarding the efficacy of the vaccine as well as out-of-pocket costs incurred by families, and uncertainty regarding the mortality and morbidity of influenza in otherwise healthy children. However, they said they would recommend the vaccine to high-risk groups (e.g. children with chronic disease(s), and asthma). Conclusion: Despite the established safety of influenza vaccines, barriers to uptake include concerns regarding the iatrogenic effects of vaccination, its administration schedule, and knowledge of influenza severity. Updated information on influenza and the efficacy of the vaccine, and incorporating influenza vaccination into the immunisation schedule may overcome some of these barriers to increase influenza vaccination in this vulnerable cohort.